2009
DOI: 10.1038/nature08604
|View full text |Cite
|
Sign up to set email alerts
|

Materials engineering for immunomodulation

Abstract: The engineering of materials that can modulate the immune system is an emerging field that is developing alongside immunology. For therapeutic ends such as vaccine development, materials are now being engineered to deliver antigens through specific intracellular pathways, allowing better control of the way in which antigens are presented to one of the key types of immune cell, T cells. Materials are also being designed as adjuvants, to mimic specific 'danger' signals in order to manipulate the resultant cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
435
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 513 publications
(441 citation statements)
references
References 101 publications
1
435
2
3
Order By: Relevance
“…In conclusion, nanomaterials can potentially play a number of roles in vaccination, to enable efficient antigen delivery and cross-presentation, reduce adjuvant dose, and translate the functionality of biologically derived materials to more robust platforms with improved shelf life and thermal stability (38). Here, the Pluronic-stabilized PPS NP material platform, based on its very small dimension (30 nm), delivers antigen very effectively to DCs in the pulmonary parenchyma, and, based on its conjugation chemistry, releases the antigen after endocytosis for optimal cross-presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, nanomaterials can potentially play a number of roles in vaccination, to enable efficient antigen delivery and cross-presentation, reduce adjuvant dose, and translate the functionality of biologically derived materials to more robust platforms with improved shelf life and thermal stability (38). Here, the Pluronic-stabilized PPS NP material platform, based on its very small dimension (30 nm), delivers antigen very effectively to DCs in the pulmonary parenchyma, and, based on its conjugation chemistry, releases the antigen after endocytosis for optimal cross-presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Two major NP parameters are considered crucial for efficient DC targeting: 1) NP size, and 2) NP surface functionalisation. Size has been shown to drastically influence particle recognition by the immune system where particles bigger than 1 µm are rapidly phagocytised by macrophages 6 . Studies performed in in vivo models have demonstrated that NPs enter lymphatic capillaries and are taken up by peripheral DCs close to the injection site with higher uptake efficiency for particles in the range of 20-200 nm 11,19 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the main potential advantages of using NPs for vaccines is based on their capacity to stabilise vaccine antigens while simultaneously acting as an adjuvant 6,[9][10] . Antigens can be encapsulated or conjugated to the NP surface, with both methods offering distinct advantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 While such morphologies elucidate the principal factors responsible for molecular self-assembly, they are likewise beneficial in various (nano)technologies. 11 These soft nanostructures, as well as their stability and thermo/(electro)mechanical properties, 12 can be fine-tuned or grossly altered through the physical incorporation of one or more solvents, 13 (co)polymers 14 or nanoparticles. 15 In the present study, the A endblocks of each ABA triblock a Author to whom correspondence should be addressed.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under mentioning
confidence: 99%